(untitled) (Research, Society and Development, 2022)
Mushrooms are cultivable on various plant substrates and the yerba mate residue may be one of the most promising, especially if domestic cultivation techniques are developed. As a large producer and consumer of yerba mate, southern Brazil also presents a large production of this residue. In this sense, this work aimed to test the cultivation of Pleurotus ostreatoroseus on yerba mate residue, seeking a technique for its domestic cultivation. Three substrates were prepared: a) partially decomposed yerba mate; b) recently discarded yerba mate; c) yerba mate recently discarded and added with eucalyptus sawdust. Cultivation of P. ostreatoroseus in yerba mate just after disposal and partially decomposed proved to be unviable, with good mycelial colonization of the substrate, but without basidioma production. In cultivation with sawdust, all concentrations tested showed the formation of primordia, with 70% of sawdust, being the first to form primordia and having the largest basidiome in diameter. It is believed that aeration is an important factor for mycelial and basidiome development in P. ostreatoroseus, contrary to what has already been mentioned for P. djamor, contributing to the differentiation of both species in cultivation situations. The mycelium of the species growing on yerba mate residue was able to reduce the inoculum of pathogenic fungi, indicating that it is an adequate practice for the treatment of the final residue. Thus, the yerba mate residue added with sawdust proved to be a possible substrate for the cultivation of P. ostreatoroseus, in addition to eliminating pathogenic fungi from plants. Keywords: Cultivation; Alternative substrates; Shimeji; Mycelial growth.